PENGARUH METODE SOSIODRAMA TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Kurniawan, Moh Wahyu; Elviana, Premita Sari Octa (P2M STKIP Siliwangi, 2021)
This study aims to analyze the effect of the sociodrama method on learning outcomes in the cognitive domain and attitude of responsibility at SMA Negeri 8 Kediri City, East Java Province. This research was conducted in learning Citizenship Education on the basic competencies of analyzing efforts to promote, respect, and enforce human rights in class X in the 2016/2017 academic year. This type of research is a quasi-experimental design with Pretest-Posttest Control Group Design. The technique of collecting data on learning outcomes is a test using multiple choice questions, while the data uses a self-assessment and peer assessment questionnaire technique. The data were analyzed using a two-sample t-test that was not correlated. The results showed that there was no significant effect of the sociodrama method with the teacher's written script on the learning outcomes of students in class X in learning Pancasila and citizenship education.